Inertial-based Fluidic Platform for Rapid Isolation of Blood-borne Pathogens. (25th January 2021) - Batcho, Erin C; Miller, Sinead; Cover, Timothy L; McClain, Mark S; Marasco, Christina; Bell, Charleson S; Giorgio, Todd D
ABSTRACT: Introduction: Bacterial sepsis is a life-threatening disease and a significant clinical problem caused by host responses to a microbial infection. Sepsis is a leading cause of death worldwide and, importantly, a significant cause of morbidity and mortality in combat settings, placing a considerable burden on military personnel and military health budgets. The current method of treating sepsis is restricted to pathogen identification, which can be prolonged, and antibiotic administration, which is, initially, often suboptimal. The clinical trials that have been performed to evaluate bacterial separation as a sepsis therapy have been unsuccessful, and new approaches are needed to address this unmet clinical need. Materials and Methods: An inertial-based, scalable spiral microfluidic device has been created to overcome these previous deficiencies through successful separation of infection-causing pathogens from the bloodstream, serving as a proof of principle for future adaptations. Fluorescent imaging of fluorescent microspheres mimicking the sizes of bacteria cells and blood cells as well as fluorescently stained Acinetobacter baumannii were used to visualize flow within the spiral. The particles were imaged when flowing at a constant volumetric rate of 0.2 mL min −1 through the device. The same device was functionalized with colistin and exposed to flowing A. baumannii at 0.2 mL h −1 . Results: Fluorescent imaging within the channel under a constant volumetric flow rate demonstrated that smaller, bacteria-sized microspheres accumulated along the inner wall of the channel, whereas larger blood cell–sized microspheres accumulated within the center of the channel. Additionally, fluorescently stained A. baumannii displayed accumulation along the channel walls in agreement with calculated performance. Nearly 10 6 colony-forming units of A. baumannii were extracted with 100% capture efficiency from flowing phosphate-buffered saline at 0.2 mL h −1 in this device; this is at least one order of magnitude more bacteria than present in the blood of a human at the onset of sepsis. Conclusions: This type of bacterial separation device potentially provides an ideal approach for treating soldiers in combat settings. It eliminates the need for immediate pathogen identification and determination of antimicrobial susceptibility, making it suitable for rapid use within low-resource environments. The overall simplicity and durability of this design also supports its broad translational potential to improve military mortality rates and overall patient outcomes.